-9b+16=-11b

Simple and best practice solution for -9b+16=-11b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9b+16=-11b equation:


Simplifying
-9b + 16 = -11b

Reorder the terms:
16 + -9b = -11b

Solving
16 + -9b = -11b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '11b' to each side of the equation.
16 + -9b + 11b = -11b + 11b

Combine like terms: -9b + 11b = 2b
16 + 2b = -11b + 11b

Combine like terms: -11b + 11b = 0
16 + 2b = 0

Add '-16' to each side of the equation.
16 + -16 + 2b = 0 + -16

Combine like terms: 16 + -16 = 0
0 + 2b = 0 + -16
2b = 0 + -16

Combine like terms: 0 + -16 = -16
2b = -16

Divide each side by '2'.
b = -8

Simplifying
b = -8

See similar equations:

| 5y^3(5y^2-7y+9)= | | 4+.20P=5+30P | | YZ=0 | | .66+.75x=.83 | | 3y-x-3=0 | | y=4x^2+32x+61 | | -4r+2=-5r+10 | | 2(y-3)=2y-9+y | | -7a-3=9+6a | | 0.4x+9.6=7.8 | | -9p+2=-7p-5-3p | | 7+2(5k+4)=-21-2k | | 5n+2=-14-n | | 18x^3=21x^2+72x | | 32m=64 | | 0.6x-1.5=8.1 | | -2m=9-5m | | 2x^4-12x^3+4x^2-38x+84=0 | | -3m=9-5m | | 42x^2-12x= | | a=b-1x-2+cx-1 | | .20(12+x)=.6+.35x | | 8x+5+3x+9+4x+4=180 | | 5z-10z=7z | | .3(12+x)=.6+.35x | | 6+p+7p=3p+6+5p | | s+2+2s-10=180 | | 10=30x+10 | | -6-5j+1=-3j+9 | | 12x-6=3(x+9) | | 13(x-2)=8x-6 | | 123456790*23456789+1234567890= |

Equations solver categories